Integrated management of sugar apple (Annona squamosa L.) - Guerrero, Eugenio de Jesús; Fischer, Gerhard (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2011)
There are several producing zones of sugar apple in Colombia, which count on ideal agro climatic conditions to develop this fruit tree; though, due to the deficient management, the production and profitability are very low. This project was aiming to implement an integrated management through a wide literature review and observations realized at the farm “El Ensueño” in Apulo (Cundinamarca); central part of Colombia. Sugar apple is native from the tropical regions of Central America or the Antilles; it is a small semi-deciduous tree growing from 3 to 7 m height. This crop grows below 1,000 m above sea level, with temperatures from minimum 10- 20ºC and to 22-28ºC max. It requires 750 to 1,000 mm of annual rainfall and relative humidity higher than 60%. It is slightly demanding soil requirements. Fruit set and productivity increase with the use of artificial pollination or liberation of pollinators. Inside the most important pest insects there are the wasp seed borer (Bephratelloides maculicollis Cam.) and the moth fruit borer (Cerconota anonella Sepp.). The most restricting diseases are the anthracnose (Colletotrichum gloeosporioides) attacking leaves, flowers and fruits and the white spot of foliage (Cercospora annonae). The fruit presents a climacteric behavior.